(untitled) (Cadernos de Sociomuseologia, 2020)
When talking about the self, what makes up a person? How far is that context not flawed by the different existing powers within such nexus? These worries are raised on my master thesis "The Marks on the Body and Power – A Sociomuseology Project", which results from my interpretation of a series of tattoos done on the skin of prisoners from the First Portuguese Republic. In this regard, the collection must be analyzed within a highly specific context, invoking concepts such as Mark, Body and Power, which are inseparable and fundamental in understanding the social sphere of the time period from which such symbols emerged. With such three concepts framed, two new ones will emerge to fundament the analysis in this collection’s context: Ethics and Sociomuseology. At this second stage, we will analyze the marks on the prisoners’ bodies from the First Portuguese Republic, the existing media of the time period, and the way dialogue was struck between them and the ruling power. Keywords: Body, Mark, Power, Ethics, Sociomuseology